IMPROVING VETERINARY SERVICES AND ENHANCING ITS MOTIVATION - E. Mitrofanova; E. Rassadina (Вестник университета)
In the agricultural economics literature evaluation of employees of veterinary services at various levels is rare, at the same time the importance of this issue is beyond doubt. The article provides one way of payroll employees of veterinary services with the performance of their work.